Throw Back on Paris Stock Exchange Delisting (2000-2019) - George El Kazzi (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
Over the past twenty years, the French stock market witnessed a lot of changes in its regulatory framework and faced new strategic decisions taken by firms when it comes to staying listed as a public company or just delist and go back to being private again. The author collected data from the Bloomberg terminal from 2000 till 2019 and the World Federation of Exchanges (WFE) and tried to analyze and differentiate among the reasons why companies decide to delist from the Euronext-Paris. A further attempt was made by retrieving data from the Euronext website and in specific the fact book from 2013 till 2019. A look deeper into delisted firms’ decisions to go back private was performed on individual delisted companies’ official publications and announcements, and the general reasons were mainly concentrated on the high cost of being listed and specially the dual listing costs, the need to overcome the burden of the minority shareholders, the low turnover of shares and the fading away of the reason for being listed in the first place presented in the need for financing.